Asset Forfeiture as A Solution for Fraudulent Investments: Insight from Indonesia and South Korea - Indah Tiara Ceisarina; Ninne Zahara Silviani; Emiliya Febriyani (Universitas Internasional Batam, 2025)
Fraudulent investment is an investment activity that offers to give a promise of maximum profit in a short time without the need to do a job that is physically, mentally and mentally exhausting and find information about the origin of the platform. Asset forfeiture by law enforcement aims to make the perpetrator fall into poverty to provide a deterrent effect and uphold a sense of justice for perpetrators of criminal acts such as money laundering. Poverty is a frightening thing in their lives. The purpose of the research is the general objective in conducting this research to find out how the recovery of asset forfeiture in handling cases of money laundering crimes. The specific objective is to analyze how the effectiveness of asset forfeiture implementation against fraudulent investment through legal comparison (Indonesia & South Korea). The research method that the author uses is in accordance with the title and relevant, so the author uses normative legal research methods. In this case, normative research is used because the characteristics of this normative legal research method are to examine legal comparisons regarding the Asset Forfeiture Law in Indonesia and South Korea. Asset forfeiture in South Korea shows effective enforcement of justice. The Indonesian people hope that this measure will be implemented to realize the 5th principle of Pancasila “Social justice for all Indonesian people” by impoverishing criminals through asset forfeiture.